1982
DOI: 10.1136/adc.57.11.842
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat treatment of cow's milk and whey on the nutritional quality and antigenic properties.

Abstract: SUMMARY Recent experiments in guinea-pigs suggest that heat treatment applied during the manufacture of baby milk formulae reduces the immunological sensitising capacity of the cows' milk proteins. This immunological benefit must be weighed against possible damage that heat treatment may cause to the nutritional quality of the products. Severe heat treatment of skimmed milk (121°C for 20 min) destroyed all the vitamin B12, about 60% of the thiamin and vitamin B6, 70% of the ascorbic acid, and about 30% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
35
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 16 publications
6
35
1
Order By: Relevance
“…High heat has been shown to cause substantial loss of several vitamins, including thiamin, vitamin B6, ascorbate, folate, and vitamin B12. The dehydro form of ascorbate, which is produced on heating milk, is involved in oxidative reactions affecting folate and vitamin B12 (Adrian, 1974;Kilshaw et al, 1982). Other investigators, however, have argued that heat treatment has no serious harmful effects on nutritional value, apart from the destruction of heat-labile vitamins, which can easily be supplemented (Langhendries et al, 1992;Angelino et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High heat has been shown to cause substantial loss of several vitamins, including thiamin, vitamin B6, ascorbate, folate, and vitamin B12. The dehydro form of ascorbate, which is produced on heating milk, is involved in oxidative reactions affecting folate and vitamin B12 (Adrian, 1974;Kilshaw et al, 1982). Other investigators, however, have argued that heat treatment has no serious harmful effects on nutritional value, apart from the destruction of heat-labile vitamins, which can easily be supplemented (Langhendries et al, 1992;Angelino et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Infant formulas are often heat sterilized in hospitals where water contamination or nosocomial infection is an issue, especially in developing countries and when large quantity of prepared milk is needed daily for nursery and hospitalized infants. However, only a few studies have investigated the effect of heat on the nutritional value of infant formula (Adrian, 1974;Kilshaw et al, 1982;Gerber et al, 1983). High heat has been shown to cause substantial loss of several vitamins, including thiamin, vitamin B6, ascorbate, folate, and vitamin B12.…”
Section: Introductionmentioning
confidence: 99%
“…Milk is treated with heat to remove microbial cells [49]. However, the heat treatment change the nutritional and flavor profile of the products [50,51]. Membrane separation techniques are operated at low temperature, which remove bacteria effectively without affecting the nutritional and flavor profile.…”
Section: Removal Of Bacteria In Milkmentioning
confidence: 99%
“…Because the amino group of amino acids, especially lysine, is blocked by the reducing sugar in the Y. Takeda. et al 574 Maillard reaction (Rufián-Henares et al, 2006;van Boekel, 1998), it is thought that heat treatment affects protein quality (Desrosiers and Savoie, 1991;Kilshaw et al, 1982;Rutherfurd and Moughan, 2005;Sarwar et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Because the amino group of amino acids, especially lysine, is blocked by the reducing sugar in the Y. Takeda. et al 574 Maillard reaction (Rufián-Henares et al, 2006;van Boekel, 1998), it is thought that heat treatment affects protein quality (Desrosiers and Savoie, 1991;Kilshaw et al, 1982;Rutherfurd and Moughan, 2005;Sarwar et al, 1988).In fact, Sarwar et al (1989) investigated the protein quality of commercial infant formulae manufactured by different production processes in a rat study, and found that the digestibility and protein efficiency ratio of the liquid formula were lower than those of the powder. In contrast, Sarriá et al (2000) investigated the protein quality of various commercial formulae, including a powdered form, an in-bottle-sterilized form and a UHT form, and reported no remarkable differences in product digestibility and protein utilization in rats.…”
mentioning
confidence: 99%